A Case of an Adult Complicated Left Diaphragmatic Hernia: Case Report and Literature Review - Ghattas, Souad; Abdel Backi, Saleem; Al Bitar, Jad; Keriakos, Kiril (International Journal of Clinical Research, 2024)
Introduction: Diaphragmatic hernia by definition is the protrusion of abdominal structures into the thoracic cavity. Classified as either congenital or acquired, adult diaphragmatic hernia without a history of trauma is rare, and iatrogenic diaphragmatic hernia is rarer. The array of symptoms may be acute or latent and will depend on the herniated organ, which certainly makes this pathology a challenge at the level of diagnosis and subsequent management. Case Report: Here we present the case of a 73-year-old male patient who presented one year post left nephrectomy complicated by splenectomy (post splenic injury), with two weeks history of diffuse abdominal pain, non-bilious vomiting, and shortness of breath. Workup done revealed a left diaphragmatic hernia containing necrotic-perforated small bowel loops. A laparotomy with intestinal resection, loop ileostomy along with a primary repair of the diaphragmatic defect were performed. Conclusion: Although a great portion of acquired diaphragmatic hernias remain asymptomatic, they may be presenting with severe symptomatology and aggravating complications. At the level of clinical manifestation, suspicion of diaphragmatic hernia ascends the ladder of differential diagnosis in a patient with combined respiratory and gastrointestinal symptoms and hence is essential to avoid delayed treatment and superimposing lethal complications. Definitive treatment of diaphragmatic hernia is surgical repair given the high morbidity and mortality associated with such injury.